Acidic pH weakens the bonding effectiveness of silane contained in universal adhesives. Issue 5 (May 2018) - Yao, Chenmin; Yu, Jian; Wang, Yake; Tang, Chuliang; Huang, Cui
Graphical abstract: Highlights: The effectiveness of silane contained in low pH universal adhesives was weakened by dehydration self-condensation. The oligomers created by self-condensation silanol would decrease bond strength. For the enhancement of glass-ceramic bonding efficiency with universal adhesives, a separate ceramic primer was recommended. Abstract: Objectives: Some silane-containing universal adhesives were introduced that a separate ceramic primer was unnecessary to glass-ceramic bonding because of incorporated silane. We aimed to investigate the effectiveness of silane in universal adhesives with acidic media. Methods: A functional γ-methacryloxypropyltrimethoxysilane (γ-MPTS) was used, and its pH value was adjusted to 2.7 by adding hydrochloric acid (HCl) or 10-methacryloxydecyl phosphate (MDP). The prepared acidic silane solutions after 2 h or 10 d storage were characterized by Fourier transform infrared spectroscopy (FTIR), 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy. Micro-shear bond strength (μSBS) was used to evaluate the bonding performance of glass ceramics. Two silane-containing and two silane-free universal adhesives were included. Field-emission scanning electron microscopy fractography analysis was also performed. Results: FTIR, 1 H and 13 C NMR revealed that the hydrolysis of γ-MPTS and the self-condensation reaction of silanol groups occurred over time under acidic conditions (HCl or MDP solution). This reaction formed the siloxane oligomers. For glass-ceramic bonding, the μSBS of acidic silane after 10 d storage was lower than that of silane stored for 2 h storage ( p  < 0.05), although the difference among the μSBS of the four universal adhesives were nonsignificant ( p  > 0.05). Additionally, cohesive failure was the main fracture pattern of universal adhesive bonding. Significance: The effectiveness of silane contained in low pH universal adhesives can be weakened by dehydration self-condensation and consequently became unstable. For the enhancement of glass-ceramic bonding efficiency with universal adhesives, a separate ceramic primer was recommended.